A new pest on soybean in Turkey: Melanagromyza sojae Zehntner (Diptera: Agromyzidae). (28th November 2019) - Özgür, O.; Bademci, M.; Büyüköztürk, H. D.
Abstract : Melanagromyza sojae Zehntner (Hemiptera: Agromyzidae) is known as a pest of several leguminous plants, especially Glycine max, soybean, in several countries worldwide. As a result of an alert raised by soybean producers in the province of Adana, which has a large share of soybean production in Turkey, plant samples in which pupae were observed were collected from two soybean fields in Çukurova in the production season in 2018. The samples were kept in the laboratory and the emerging adults were identified morphologically as M. sojae . Observations made in soybean fields in Turkey are presented. A review of the situation for this pest and its control methods are is presented. This is the first report of M. sojae in Turkey. It is therefore recommended to perform a close monitoring of this pest to investigate more in detail the extent of the damage caused by this pest in soybean crops in Turkey, to identify its variety preferences, other other hosts, natural enemies and control methods to be used. Nouvel organisme nuisible du soja en Turquie : Melanagromyza sojae Zehntner (Diptera : Agromyzidae): Melanagromyza sojae Zehntner (Hemiptera : Agromyzidae), ou agromyze des tiges du soja, est un organisme nuisible de plusieurs espèces de légumineuses et en particulier du soja ( Glycine max ), dans divers pays à travers le monde. À la suite d'une alerte lancée par les producteurs de soja de la province d'Adana, région produisant une part importante du soja en Turquie, des échantillons de plantes contenant des pupes ont été prélevés dans deux champs de soja situés à Çukurova pendant la saison de production 2018. Les échantillons ont été conservés en laboratoire et les adultes émergents ont été identifiés sur la base de critères morphologiques comme étant M. sojae . Les observations faites dans les champs de soja, ainsi qu'une revue de la situation de cet organisme nuisible et des stratégies de lutte disponibles contre cet organisme nuisible sont présentées dans cet article. Il s'agit du premier signalement de M. sojae en Turquie. Ainsi, un suivi de cet organisme doit être réalisé afin d'évaluer les dégâts causés par l'organisme nuisible dans les cultures de soja en Turquie, et identifier ses préférences variétales, ses différents hôtes, ses ennemis naturels et les mesures de gestion à utiliser. Новый вредный организм на сое в Турции : Melanagromyza sojae Zehntner (Diptera: Agromyzidae): Melanagromyza sojae Zehntner (Hemiptera: Agromyzidae) известен как вредитель нескольких бобовых культур, особенно сои Glycine max, в нескольких странах мира. В результате сигнала, полученного от производителей соевых бобов в провинции Адана (на долю которой приходится большая часть производства соевых бобов Турции), в вегетационный сезон 2018 года с двух соевых полей в Чукурова были собраны образцы растений, в которых были обнаружены пупарии. Образцы содержались в лаборатории, и отродившиеся имаго были морфологически идентифицированы как M. sojae . Представлены данные наблюдений, полученных на полях сои. Представлен обзор ситуации с этим вредителем и методы борьбы с ним. Хотя масштабы ущерба, причиненного M. sojae (зарегистрированого впервые в Турции), пока не известны, необходим тщательный мониторинг. Ущерб, наносимый вредителем на культурах сои, предпочитаемые им сорта, другие хозяева, естественные враги и методы борьбы нуждаются в более подробном изучении.